A nexus approach to support natural resource management in the Blue Nile Basin of Ethiopia - Balcha, Yodit; Taye, Meron Teferi; Getaneh, Yonas; Abera, Wuletawu (CGIAR, 2023)
In Ethiopia’s Tana-Beles region, water, energy, food and ecosystems (WEFE) are tightly interconnected, making a nexus approach highly relevant. Through the CGIAR Initiative on NEXUS Gains, researchers from the Alliance of Bioversity-CIAT and the International Water Management Institute (IWMI) have been working on nexus tools, including the FABLE calculator and scenario tool at the national level, and the integrated water storage diagnostic in the Tana-Beles, a sub-basin of the Blue Nile River Basin.